Connectivity, Accessibility, and Mobility Relationships in the Context of Low-Volume Road Networks. Issue 12 (December 2019) - Labi, Samuel; Faiz, Asif; Saeed, Tariq Usman; Alabi, Bortiorkor Nii Tsui; Woldemariam, Wubeshet
The concepts of connectivity, accessibility, and mobility (CAM) are key measures of transport network performance that have been discussed extensively in the literature. However, there has been little work that discussed the relationships among these concepts. A clear discourse on these concepts and their interrelationships can help agencies carry out more objective evaluations of projects that seek to improve at least one of these measures of transportation performance. This paper presents three alternative perspectives (models) of the CAM relationship: the nested, snowman, and three-way overlapping models. The paper also presents, for project appraisal purposes, two alternative ways of classifying the three CAM concepts. The first is based on the three concepts in their basic forms; the second considers some variation of these concepts in addition to aspects of the network topology, operational performance, road condition, and socioeconomic characteristics of the project's area of influence. The conceptual framework outlined in this paper contributes towards a holistic approach to the appraisal of low-volume road projects, programs, or existing networks based on their impact on overall CAM.